The Snapshot of Online Public Relations in Indonesia Public Agencies: Effort to Comply With Conditions of Pita (Quantitative Study on Content Analysis of The Websites of Public Agencies That Receive Public Information Transparency Award in 2016) - Syaiful Azhary; Rachmat Kriyantono; Maulina Pia Wulandari (Sekolah Pascasarjana Universitas Brawijaya, 2017)
In this age of public information transparency, website characteristic has been a representation of online public relations of Indonesia public agencies based on which public agencies are required to provide transparent and accountable information, and therefore, online public relations helps them to make available a dialogic space for public and agency, which then reducing information gap. This paper promoted a theme of the evaluation on Indonesia public agencies’ online public relations in effort to measure the transparency and accountability of information given to the public. This theme was subjected to examination with positivism approach and quantitative method and then explained descriptively based on the criteria of 4 models of evaluation using Website Attribute Evaluation System (WAES). Content analysis was conducted and focused on the systematic features of the website. Research used proportional stratified random sampling based on the rating of information transparency of public agencies in 2016. Result of research indicates that still quite few public agencies have features of transparency, interactivity, usability, and website maturity, and thus, information gap still exists and is obviously influencing public’s perception and expectation, which then affecting public trust to public agencies.